2014
DOI: 10.3354/esr00631
|View full text |Cite
|
Sign up to set email alerts
|

Energy content of Pacific salmon as prey of northern and southern resident killer whales

Abstract: Recovery of depleted species is difficult, but it can be especially complex when the target species interacts strongly with other depleted species. Such is the case for northern and southern resident killer whales Orcinus orca which are listed as 'endangered' under the US Endangered Species Act (ESA) and Canada's Species at Risk Act. These resident killer whales prey heavily on Pacific salmon Oncorhynchus spp., including several 'evolutionarily significant units' also listed under the ESA. In response to conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 39 publications
3
39
2
Order By: Relevance
“…Importantly, Spitz and Jouma'a (2013) found that the species with the highest energy density values were also the species with the highest seasonal and inter-annual variability in energy density. O'Neill et al (2014) also found that the same species of salmon varied in energy density based on the population sampled. Analyzing the variation of energy density at different temporal and geographic scales for the highest energy fish found in this study would be valuable to ascertain a more accurate picture of energy availability to the dolphins.…”
Section: Seasonal Energy Content and Prey Qualitymentioning
confidence: 83%
See 1 more Smart Citation
“…Importantly, Spitz and Jouma'a (2013) found that the species with the highest energy density values were also the species with the highest seasonal and inter-annual variability in energy density. O'Neill et al (2014) also found that the same species of salmon varied in energy density based on the population sampled. Analyzing the variation of energy density at different temporal and geographic scales for the highest energy fish found in this study would be valuable to ascertain a more accurate picture of energy availability to the dolphins.…”
Section: Seasonal Energy Content and Prey Qualitymentioning
confidence: 83%
“…Other marine mammal populations are likely influenced by the quality of prey available. Endangered resident killer whales (Orcinus orca) in the north-eastern Pacific preferentially forage on Chinook salmon (Oncorhynchus tshawytscha; Ford et al, 1998;Ford and Ellis, 2006), which have the highest energy values of the five species of Pacific salmon, yet occur in the lowest abundance (O'Neill et al, 2014). Common dolphins (Delphinus delphis) also select prey with the highest energy density (>5 KJ g −1 ) and seem to ignore the most abundant species, which were of lower energy density (<5 KJ g −1 ) (Spitz et al, 2010a).…”
Section: Seasonal Energy Content and Prey Qualitymentioning
confidence: 99%
“…Chinook Salmon Oncorhynchus tshawytscha , which must endure longer, more arduous migrations, typically have higher energy content (Quinn ; O'Neill et al. ). Female salmon have higher energetic demands than males do because they need to produce energy‐rich eggs and thus require additional lipid stores for successful migration and spawning activities (Kinnison et al.…”
mentioning
confidence: 99%
“…The energy content of eels in this study was higher than previous studies in several salmon (chinook, sockeye, coho, pink and chum salmon) that containing energy 100-170 KCal.100g -1 . (O'Neill et al, 2014). Porto et al (2016) reported that energy content of captured fish in Itapecuru river Maranhao Brazil was lower (77-136 KCal.100g -1 .…”
Section: Energy Contentmentioning
confidence: 99%
“…Energy in food can be estimate through protein, fat and carbohydrate content. O'Neill et al (2014) explained that energy of lipid and protein tissues were estimated separately for each composite whole body sample by multiplying the lipid and protein wet mass (percent tissue × average mass of fish in the composite) by the average energy equivalents in each tissue type (lipid= 9 KCal g −1 , protein= 4 KCal g −1 ).…”
Section: Energy Contentmentioning
confidence: 99%